(3WHbGJ GdNhGU Cgd GdUOb hGdENdGUs - (3GdRHjOj , CMeO Hf CMeO Hf YHO GddWja GdTQLj, TgGH GdOjf,J (B893 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdeJaVd HLRjd GdehGgH hGdYWGA CeG HYO aEfi hbaJ Ydi LedI ef GdcJH GdeUfaI ai PcQ ChdjGA Gddg JYGdi s
(3BNQgG (B:s
(3bGd eDdag Je Pdc HJGQjN TgQ ThGd GdeHGQc ef SfI SHY hSJjf hKeGfeGFI hGdMeO ddg cKjQkG (B" [ (3hjdi gPG ChQGb JJVef eG bjd ai GdWHbGJ fKQkG hfXekG s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B91 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B150s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs